Constructing Chromium Multioxide Hole‐Selective Heterojunction for High‐Performance Perovskite Solar Cells. Issue 30 (28th August 2022) - Jiang, Sheng; Xiong, Shaobing; Dong, Wei; Li, Danqin; Yan, Yuting; Jia, Menghui; Dai, Yannan; Zhao, Qingbiao; Jiang, Kai; Liu, Xianjie; Ding, Liming; Fahlman, Mats; et al.
Abstract: Perovskite solar cells (PSCs) suffer from significant nonradiative recombination at perovskite/charge transport layer heterojunction, seriously limiting their power conversion efficiencies. Herein, solution‐processed chromium multioxide (CrOx ) is judiciously selected to construct a MAPbI3 /CrOx /Spiro‐OMeTAD hole‐selective heterojunction. It is demonstrated that the inserted CrOx not only effectively reduces defect sites via redox shuttle at perovskite contact, but also decreases valence band maximum (VBM)‐HOMO offset between perovskite and Spiro‐OMeTAD. This will diminish thermionic losses for collecting holes and thus promote charge transport across the heterojunction, suppressing both defect‐assisted recombination and interface carrier recombination. As a result, a remarkable improvement of 21.21% efficiency with excellent device stability is achieved compared to 18.46% of the control device, which is among the highest efficiencies for polycrystalline MAPbI3 based n–i–p planar PSCs reported to date. These findings of this work provide new insights into novel charge‐selective heterojunctions for further enhancing efficiency and stability of PSCs. Abstract : Solution‐processed chromium multioxide hole‐selective heterojunction boosts power conversion efficiency and stability of perovskite solar cells.